2014
DOI: 10.1186/2047-9158-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trials in frontotemporal dementia: cognitive and behavioral outcomes

Abstract: Progress has been made in understanding the genetics and molecular biology of frontotemporal dementia (FTD). Targets for intervention have been identified, therapies are being developed, and clinical trials are advancing. A major challenge for FTD research is that multiple underlying pathologies can be associated with heterogeneous phenotypes. The neuropsychological profiles associated with FTD spectrum disorders often include executive dysfunction, language impairments and behavioral disturbance. Behavioral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Knecht, Wersching, Lohmann, Berger, & Ringelstein (2009) reported that up to 11% of age-related changes in memory, executive function, attention, and verbal fluency were linked to systolic blood pressure. It is also consistent with clinical evidence that the MoCA is sensitive to frontal and frontotemporal dementia (Chertkow, Nasreddine, Philips, Litwin, & Whitehead, 2010;Freitas, Simões, Alves, Duro, & Santana, 2012;Miller, Banks, L eger, & Cummings, 2014), as well as MCI and Alzheimer's disease. It is possible to use the MoCA to extract measures related to specific cognitive domains (e.g., episodic memory, executive functioning, and attention; Dong et al, 2010;Nie et al, 2012;Wester, Westhoff, Kessels, & Egger, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Knecht, Wersching, Lohmann, Berger, & Ringelstein (2009) reported that up to 11% of age-related changes in memory, executive function, attention, and verbal fluency were linked to systolic blood pressure. It is also consistent with clinical evidence that the MoCA is sensitive to frontal and frontotemporal dementia (Chertkow, Nasreddine, Philips, Litwin, & Whitehead, 2010;Freitas, Simões, Alves, Duro, & Santana, 2012;Miller, Banks, L eger, & Cummings, 2014), as well as MCI and Alzheimer's disease. It is possible to use the MoCA to extract measures related to specific cognitive domains (e.g., episodic memory, executive functioning, and attention; Dong et al, 2010;Nie et al, 2012;Wester, Westhoff, Kessels, & Egger, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Identification of effective, evidence-based symptomatic treatments for social cognition and behaviour deficits in FTD and other neuropsychiatric disorders raises several unique challenges for clinical trial design and implementation. These challenges include symptom and behavioural heterogeneity, the nonlinear trajectory of many behavioural symptoms over the course of the disease, lack of harmonisation of assessment and outcome measures across centres, and reliance on subjective caregiver reports for key outcome measures [ 2 4 ]. Additional challenges for randomised controlled trials (RCTs) of oxytocin include potential differential responses according to sex, uncertainties around brain penetration of intranasal formulations, lack of dose-finding studies, and confirmation of target engagement [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…FTD treatment strategies generally rely on the use of medications for symptomatic management, but most therapies lack quality evidence from randomized, placebo-controlled clinical trials (150). Selective serotonin reuptake inhibitors may be effective in the case of behavioral symptoms, while antipsychotics or antiepileptic drugs are also effective in some case reports, but use of these latter agents is limited by the concern of side effects.…”
Section: Clinical Treatment Of Ftdmentioning
confidence: 99%